The Effect Of Halal Labelization And Brand Image On Tourism Decisions In Demak District - Heru Yulianto; Dyah Palupiningtyas; Mudrik Mudrik; Amsar Amsar (Politeknik APP Jakarta, 2023)
This study aims to determine the effect of halal labeling on travel decisions in Demak Regency and to determine the effect of brand image on decision making traveling in Demak Regency. This type of research is qualitative and the research design aims to test hypotheses or explain the influence between variables (Indriantoro, et al., 2002:89). The population of this research is all consumers who travel in Demak Regency. Sampling was done by convenience sampling technique, namely collecting information from members of the population who are happy to provide information. Based on the results of research and hypothesis testing, it can be concluded that Brand Labeling has a positive contribution to Tourism Decisions in Demak Regency. Brand Image contributes positively to tourism decisions in Demak district.